Pengaruh Dewan Komisaris Independen, Komite Audit, Leverage Dan Profitabilitas Terhadap Manajemen Laba (Studi Empiris Pada Perusahaan Terbuka Sektor Industri Barang Konsumsi) - Setyani, Putri Yunita; Suhaili, Achmad (JURNAL BISNIS DAN PEMBANGUNAN, 2023)
Committees, leverage, and profitability on earnings management of Manufacturing companies (consumer goods) listed in the Indonesia Stock Exchange (IDX) for the period of  2016 - 2018. The type of this research is associative quantitative researchthat aims to analyze the relationships between variables. Sample of this research consisted of 27 companies selected by the purposive sampling method. Output of this research are (1) There are indicates that earnings management is not influenced by the independent commissioners and the audit committees. (2) Leverage and profitability have an influence on earning management Keywords: Independent Board of Commissioners, Audit Committee, Leverage, Profitability, Earning Management